AKTIVITAS ANTIOKSIDAN DAN KARAKTERISASI ISOLAT DARI FRAKSI n-HEKSANA PADA RUMPUT LAUT (Caulerpa sertularioides) ASAL SINGKAWANG KALIMANTAN BARAT (ANTIOXIDANT ACTIVITY AND ISOLATE CHARACTERIZATION OF n-HEXANE FRACTION IN SEAWEED (Caulerpa sertularioides) FROM SINGKAWANG WEST KALIMANTAN) - Fitriani Fitriani; Endah Sayekti; Ajuk Sapar (Tanjungpura University, 2022)
Seaweed (Caulerpa sertularioides) is one of the marine plants of West Kalimantan, which contains bioactive compounds that can act as antioxidants. The purpose of this study was to determine antioxidant activity and identify components of organic compounds in seaweed C. sertularioides. This research was carried out in several stages, namely extraction, fractionation, antioxidant test (DPPH), vacuum liquid chromatography (KVC), gravity column chromatography (KKG), and two-dimensional thin-layer chromatography (2-Dimensional TLC), and characterization. Antioxidant activity test by DPPH method on methanol extract, n-hexane fraction, and fraction DCM from seaweed C. sertularioides obtained IC50 values of 82.21 g/mL (strong antioxidant), 131.2 g/mL (medium antioxidant), and 192.43 g/mL (weak antioxidant). The results of the FT-IR identification of isolate I4 showed a strong absorption at 3483-3387 cm-1,which was specific for the OH group. The presence of strong absorption of 2926-2854cm-1 C-H stretching group, a wide absorption of 1338 cm-1 of methyl and methylene groups (stretching). There was a strong absorption of 1543-1463 cm-1 C-O ester group (bend), a broad absorption of 1074 cm-1 C-O (stretching), and absorption of 1795-1735 cm-1 specific for the C=O ester group. The results of GC-MS on isolate I4 indicated the main component was compound 1-nonadecene (14.09%), Trifluoroacetoxy hexadecane based on the literature, the compound included the organic component of fatty acids, and esters